Chromosome‐level genome assembly of the aphid parasitoid Aphidius gifuensis using Oxford Nanopore sequencing and Hi‐C technology. (13th January 2021) - Li, Bingyan; Du, Zhenyong; Tian, Li; Zhang, Limeng; Huang, Zhihua; Wei, Shujun; Song, Fan; Cai, Wanzhi; Yu, Yanbi; Yang, Hailin; Li, Hu
ABSTRACT: Aphidius gifuensis is a parasitoid wasp that has been commercially bred and released in large scale as a biocontrol agent for the management of aphid pests. As a highly efficient endoparasitoid, it is also an important model for exploring mechanisms of parasitism. Currently, artificially bred populations of this wasp are facing rapid decline with undetermined cause, and mechanisms underlying its parasitoid strategy remain poorly understood. Exploring the mechanism behind its population decline and the host–parasitoid relationship is impeded partly due to the lack of a comprehensive genome data for this species. In this study, we constructed a high‐quality reference genome of A. gifuensis using Oxford Nanopore sequencing and Hi‐C (proximity ligation chromatin conformation capture) technology. The final genomic assembly was 156.9 Mb, with a contig N50 length of 3.93 Mb, the longest contig length of 10.4 Mb and 28.89% repetitive sequences. 99.8% of genome sequences were anchored onto six linkage groups. A total of 11, 535 genes were predicted, of which 90.53% were functionally annotated. Benchmarking Universal Single‐Copy Orthologs (BUSCO) analysis showed the completeness of assembled genome is 98.3%. We found significantly expanded gene families involved in metabolic processes, transmembrane transport, cell signal communication and oxidoreductase activity, in particular ATP‐binding cassette (ABC) transporter, Cytochrome P450 and venom proteins. The olfactory receptors (ORs) showed significant contraction, which may be associated with the decrease in host recognition. Our study provides a solid foundation for future studies on the molecular mechanisms of population decline as well as host–parasitoid relationship for parasitoid wasps.